On form-factor expansions for the XXZ chain in the massive regime. (28th May 2015) - Dugave, Maxime; Göhmann, Frank; Kozlowski, Karol K; Suzuki, Junji
Abstract: We study the large-volume- L limit of form factors of the longitudinal spin operators for the XXZ spin-1/2 chain in the massive regime. We find that the individual form factors decay as L − n, n being an even integer counting the number of physical excitations—the holes—that constitute the excited state. Our expression allows us to derive the form-factor expansion of two-point spin–spin correlation functions in the thermodynamic limit L → +∞. The staggered magnetisation appears naturally as the first term in this expansion. We show that all other contributions to the two-point correlation function are exponentially small in the large-distance regime.